“Liquid Biopsy” of White Matter Hyperintensity in Functionally Normal Elders - Elahi, Fanny M.; Casaletto, Kaitlin B.; Altendahl, Marie; Staffaroni, Adam M.; Fletcher, Evan; Filshtein, Teresa J.; Glymour, Maria M.; Miller, Bruce L.; Hinman, Jason D.; DeCarli, Charles; Goetzl, Edward J.; Kramer, Joel H. (Frontiers in Aging Neuroscience, 2018)
Background and Objective: In the aging brain, increased blood-brain barrier (BBB) leakage and white matter hyperintensity (WMH) on MRI are frequently presumed secondary to cerebral small vessel disease (cSVD) or endotheliopathy. We investigate this association in vivo, by quantifying protein cargo from endothelial-derived exosomes (EDE), and comparing levels between two groups of functionally normal elders with and without WMH. In addition, we study associations of EDE proteins with upstream and downstream factors, such as inflammation and neurodegenerative changes, respectively. Methods: 26 neurologically-normal older adults completed general health questionnaires, neuropsychological and physical examinations, and brain MRI. WMH was visually graded with modified Fazekas score >=2 used to classify 11 subjects as cases, and 15 without WMH as controls. Plasma total exosomes were precipitated and EDEs enriched by sequential immuno-precipitations. In addition, we quantified three inflammatory cytokines from plasma, and imaging variables on MRI. Group means were compared, the discriminant functions of biomarkers calculated, and the association of EDE biomarkers with plasma inflammatory markers, cognition, and imaging outcomes assessed via regression modelling. Results: Brain-expressed EDE cargo proteins (GLUT1, LAT1, P-GP, NOSTRIN) were significantly higher in subjects with WMH in comparison to those without. In contrast, EDE levels of the marker with low expression in brain (VCAM1) were equal between groups. The effect sizes for each of these cargo proteins was such that age-adjusted logistic regressions revealed areas under the curve (AUC) ranging .8-.89 differentiating subjects with WMH from those without. VCAM1 poorly discriminated between groups (AUC:0.55). Higher levels of all brain expressed EDE proteins were also associated with lower cognitive function, unrelated to burden of WMH. Levels of LAT1 and P-GP were significantly inversely associated with global grey matter volumes, and EDE GLUT1, LAT-1, and P-GP concentrations were significantly associated with systemic IL6 levels. Conclusions: In a case control study of clinically normal adults with and without WMH, concentrations of EDE proteins were significantly higher in subjects with WMH in comparison to controls. This work is a first step toward in vivo dissection of molecular changes in endothelia of functionally normal subjects with radiographic evidence of age-associated white matter disease.